Asunaprevir/daclatasvir and sofosbuvir/ledipasvir for recurrent hepatitis C following living donor liver transplantation. Issue 11 (15th December 2016) - Omichi, Kiyohiko; Akamatsu, Nobuhisa; Mori, Kazuhiro; Togashi, Junichi; Arita, Junichi; Kaneko, Junichi; Hasegawa, Kiyoshi; Sakamoto, Yoshihiro; Kokudo, Norihiro
Abstract : Aim: This study aimed to clarify the efficacy and safety of interferon‐free therapy using asunaprevir and daclatasvir, or sofosbuvir and ledipasvir for post living donor liver transplantation (LDLT) recipients with hepatitis C virus (HCV). Methods: A retrospective cohort study of LDLT recipients with HCV genotype 1b treated with asunaprevir (100 mg twice daily) and daclatasvir (60 mg once daily), or sofosbuvir (400 mg/day) and ledipasvir (90 mg/day) was carried out. Results: Ten patients without mutations in the area of L31 and Y93 completed the treatment with asunaprevir and daclatasvir. Five of them had end‐stage chronic kidney disease, including three hemodialysis patients. Of the 10 patients, nine completed the protocol of 24 weeks; one stopped the treatment due to the development of aortic valve stenosis. All nine patients who completed the 24‐week treatment protocol achieved end of treatment response. Nineteen patients received treatment with sofosbuvir and ledipasvir. Of the 19 patients, 18 completed the protocol of 12 weeks; one stopped treatment due to severe interstitial pneumonia. All 18 patients who completed the 12‐week treatment protocol achieved end of treatment response. All patients in both treatment groups who completed the regimen and reached 3 months after the end of treatment achieved sustained virological response at 12 weeks after treatment. Liver functions were significantly improved at the end of treatment, and no adverse events were observed. Conclusions: Interferon‐free therapy using asunaprevir and daclatasvir, or sofosbuvir and ledipasvir, is highly effective for post‐LDLT recipients with HCV genotype 1b.